Invoking humanity : war, law and global order - Zolo, Danilo (Political theory and contemporary politics., 2002)
* Powerful, passionate and highly topical critique of humanitarian intervention* International political theorist with eight top-selling books""Whoever invokes humanity wants to cheat.""In this first time translation in English, Danilo Zolo considers Carl Schmitt''s maxim in the context of the ""humanitarian war"" waged against the Federal Republic of Yugoslavia in the Spring of 1999 by 19 NATO countries. This erudite and disturbing book is a political, legal and philosophical reflection on an extraordinary display of Western Power and its present and future impact on the global system of inte